The Live Shopping Phenomenon on TikTok and its Impact on Local MSMEs (Study on Thrifting Traders in Gedebage Market, Bandung City) - Vina Qurrotu A'yuni; Syifa Ramadhani Asmi; Sulthan Ariq Wibisana (Journal Social Society, 2025)
The development of digital technoslogy has changed the landscape of commerce, including the rise of live shopping features on TikTok. This study aims to examine the response of thrift MSME players in Gedebage Market, Bandung, to the TikTok Live trend. Different from previous studies that focus on new products, this research highlights thrift MSMEs that have not been widely researched. The method used is qualitative through in-depth interviews, observation, and media content analysis. The results show that Pasar Gedebage is a vibrant informal economy ecosystem, but digital adoption (especially TikTok Live) is still limited due to barriers of technological capital, digital literacy, and cultural resistance. Although social media has great potential as a promotional tool, its utilisation is still sporadic. In conclusion, thrift MSME players have not fully utilised TikTok Live and rely more on conventional methods. Support through informal networks and mentoring between business actors is needed to encourage adaptation to the digital economy.